X-ray Diffraction Phase Analyses of Mullite Derived from Rice Husk Silica - Sembiring, Simon; Simanjuntak, Wasinton (Makara Journal of Science, 2012)
X-ray Diffraction Phase Analyses of Mullite Derived from Rice Husk Silica